Penggunaan Arbitrage Pricing Theory untuk Menganalisis Return Saham pada Perusahaan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2015-2021 - Fitri Halimatus Sahdiah; Fitriani Komara (Reviu Akuntansi, Manajemen, dan Bisnis, 2022)
Purpose: This research aimed to find out and analyze the impact of inflation, exchange rates, and gross domestic product to the stock returns on the banking companies listed on the Indonesian stock exchange (IDX) from2015 to 2021. Method: The sample collection technique used in this study was purposive sampling technique with a total sample of 29 samples of banking companies. The research used descriptive and associative data analysis methods. The data analysis technique used is panel data regression analysis technique and using secondary data sources. Results: The study results with simultaneous hypothesis testing showed that the inflation, exchange rates, and gross domestic product had a significant influence on the stock returns. Partial testing of the hypothesis showed that the exchange rates had a negative influence on the stock returns. Inflation and GDP there is no significant on the stock returns. Limitations: Returns based on the difference in stock prices at the end of the year, using macroeconomic factors that are often used, are limited to companies in the banking sub-sector for the 2015-2021 period, and the value of determination is 16.99%, which means that there are many other factors that affect stock returns. Contribution: This research can be used for adding knowledge in the investing, especially in the capital market, so as to minimize errors in investment decision making and consideration in investment activities in banking companies.